Novel Treatment Options in Metastatic Esophageal Carcinoma: Checkpoint Inhibitors in Combination Therapies - Casari, Capucine; Novysedlak, Rene; Vachtenheim, Jiri; Lischke, Robert; Strizova, Zuzana (Pharmacology, 2023)
BACKGROUND: Metastatic esophageal carcinoma (EC) has a poor prognosis and only limited treatment options. While immune checkpoint inhibitors (ICIs) have improved the treatment of a broad spectrum of cancers, patients with EC mostly fail to respond to this treatment. For that reason, it is crucial to understand the immune phenotype of each cancer patient and moreover, to understand how different therapies modulate the cancer microenvironment and sensitize the tumors to the treatment with ICIs. SUMMARY: We have conducted a systematic review of the literature to evaluate the potential of ICI therapy in combination with chemotherapy, radiotherapy, and/or biologic therapy in EC patients. In our review, we have discussed the effects of diverse treatment approaches on the tumor microenvironment of EC. In addition, we have reviewed the current phase II and III clinical trials in EC patients to provide a rationale for immunotherapy application in combination settings with chemotherapy, radiotherapy, and/or biologic therapy. KEY MESSAGES: A great effort is already underway in clinical trials evaluating the combinatorial administration of ICIs and other treatment modalities in metastatic EC patients. PD-L1 expression status was shown to be higher in the squamous cell carcinoma (SCC) as compared to adenocarcinoma. Thus, ICIs plus chemotherapy are being discussed as a particularly feasible option for patients with SCC. Radiation was shown to induce the expression of immune checkpoint molecules and to promote the priming and activation of cytotoxic T cells which provides a rationale for ICI administration in a combination with radiotherapy. The combination of ICIs with biologic therapy was shown to be safe; however, the impact on the clinical outcomes of EC patients varied among studies.
Keywords: karcinom; imunoterapie; nádorové mikroprostředí; Immunotherapy; nádory jícnu; lidé; Tumor Microenvironment; Carcinoma; Esophageal Neoplasms; Humans